Scan-rate and vacuum pressure dependence of the nucleation and growth dynamics in a spin-crossover single crystal: the role of latent heat. Issue 14 (26th March 2018) - Ridier, Karl; Rat, Sylvain; Salmon, Lionel; Nicolazzi, William; Molnár, Gábor; Bousseksou, Azzedine
Abstract : A heat exchange dependence was evidenced on both the hysteresis properties and the switching dynamics of a spin-crossover single crystal. Abstract : Using optical microscopy we studied the vacuum pressure dependence (0.1–1000 mbar) of the nucleation and growth dynamics of the thermally induced first-order spin transition in a single crystal of the spin-crossover compound [Fe(HB(tz)3 )2 ] (tz = 1, 2, 4-triazol-1-yl). A crossover between a quasi-static hysteresis regime and a temperature-scan-rate-dependent kinetic regime is evidenced around 5 mbar due to the change of the heat exchange coupling between the crystal and its external environment. Remarkably, the absorption/dissipation rate of latent heat was identified as the key factor limiting the switching speed of the crystal.